Book Review. Issue 2 (August 2016) - Southall, Roger
Michael Bratton (2014), Power Politics in Zimbabwe, Scottsville, Pietermaritzburg: University of KwaZulu-Natal Press, ISBN 978186914 3114, 280 pp. David Coltart (2016), The Struggle Continues: 50 Years of Tyranny in Zimbabwe, Auckland Park: Jacana Media, ISBN 9781431423187, 646 pp.